Students’ Perspectives towards Wasatiyyah Course: A Case Study in Universitas Islam Internasional Indonesia - Siregar, Nurhalimah; Abdul Aziz, Muhammad (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
The Islamic concept of wasatiyyah is reflected in the Qur’an that states the Muslim community as ummatan wasatan. It means that Muslim should be in the middle path in many aspects of live, which avoid from the extremist and neglecting. In doing so, education plays a significant role to promote the concept of wasatiyyah. However, its neglected from the teaching and learning of Islamic education. This study aimed to explore the implementation of wasatiyyah course in Universitas Islam Internasional Indonesia. The study conducted qualitatively with a case study research design in investigating students’ perspectives on the wasatiyyah course. A total of four participants from different faculties and countries are participated in this study. The data was collected through semi-structured interview and analyzed with the Miles and Huberman framework. Overall, the result of the study shows that student perceive positively towards the course of wasatiyyah Islam. In addition, the study also demonstrates students’ reflection on the practice of the concept wasatiyyah in plural context. Hence, it recommended reimaging the concept of wasatiyyah in Islamic universities by implementing the idea into course subject to promote the tolerance and harmony within the diversity